Die Voortrekkerideaal - Natal of Transvaal? - Oberholzer, J. P. (Hervormde teologiese studies, 1989)
The Voortrekker ideal - Natal or Transvaal? On the basis of several documents from prominent Voortrekker leaders their ideal is summarised as follows: They were seeking for a space in which they could enjoy responsible freedom together with a means of living, an d could sustain their freed om by self government, good relations with other peoples and defence of person, land and property. From the inception of the idea of emigration the ultimate distination was seen differently by leaders, but eventually it was the Transvaal which provided the first real fulfillment of the ideal in the form of independence acknowledge by Great Britain.